Dinamika Peran Pacalang Dalam Menunjang Aktivitas Kepariwisataan di Desa Adat Tuban-Kuta - I Wayan Wesna Astara; I Made Mardika (Lembaga Penelitian, Universitas Warmadewa, 2017)
The dynamics of the Pecalangâ€™s role in the Traditional Village of Tuban has experienced multifunctional roles after the splendor of the tourism activities happened in the village. As a tourism area that is supported by Ngurah Rai International Airport and heterogeneous and multicultural population, this traditional village requires an arrangement of the socialreligious institution of Pecalang, the Village Security Forces that are in synergy with the Civil Defense (Hansip). The problems that arose in this research were 1). How the form of the Pecalang in supporting the tourism activities in the traditional village of Tuban was?; 2). How the implications of the Pecalangâ€™s involvement in supporting the tourism activities in the village was? The method of approach with the type of the qualitative research, that is, the analysis of field data collection with consideration of the nature and scope of the research problems is in the characteristic of multidisciplinary. Based on the results of the research, it can be described that the multifunctional role of the Pecalang is empirically in synergy with the Security Forces of the traditional village (Hansip). The Pecalang and the Security Forces of the village altogether form a single integrated post to maintain the security, tranquility, and the orderliness at the traditional village of Tuban. The role of the Pecalang in the tourism of a pluralistic community is at the beginning in the domain of â€œreligion,â€ custom, and culture, then flows to the domain of â€œstateâ€/security and to the social-economic function of tourism activities. In the real juridical, the formation of Pecalang and the Security Forces of the village was just written in the village role â€œPenyacahâ€ when the traditional village followed village a contest of traditional villages in the level of Badung Regency in 2016. At that time, there was a mistake to put the role of the Security Forces of the village and the Pecalang. The role of the village Security Forces and the Pecalang should be not in the role of â€œPenyacah, but in the role of â€œNyejeâ€ or â€œNgeleâ€/ the released role. Key word: Pecalang, multifunction, tourism , village role